Amalan pengurusan keselamatan dan tingkahlaku keselamatan dalam kalangan pekerja di dalam industri automotif di Malaysia - Zailatul Fais, Mohd Noor (2017)
Good safety management practices can affect work conditions, motivations, and safety behaviors and consequently reduce unintentional accident and incidents. This study was conducted to determine the effects of independent variables ie management commitment, safety training, employee engagement and safety communications and feedback on dependent variables ie safety behavior on workers in a factory in the automotive industry in Nilai, Negeri Sembilan. This quantitative study uses a questionnaire distributed to 132 automotive factory workers in order to answer the research questions. Multiple regression analysis is used and shows three of the safety management practices namely safety behavior, employee engagement and safety communications and feedback have relationship with safey behavior. Whereas, management commitment factor did not influence the safety behavior at workplace. The findings can provide guidance for researchers nor practitioners in identifying which mechanisms can enhance safety at work.